Green synthesis of GO-loaded Ag/ZnO nanocomposites for methyl orange degradation - Nadargi, Digambar Y.; Nadargi, Jyoti D.; Tamboli, Mohaseen S.; Tamboli, Asiya M.; Mulla, Imitaz S.; Umar, Ahmad; Truong, Nguyen Tam Nguyen; Suryavanshi, Sharad S. (Journal of Materials Science-Materials in Electronics, 2023)
Nature is a perfect laboratory for creating novel nanomaterials for a variety of applications. A robust green synthesis approach to GO-loaded Ag/ZnO nanocomposite materials using medicinal plant extraction and their potential application in methyl orange dye degradation are reported. The straightforward technique employs zinc and silver nitrate precursors in an aqueous solution of medicinal plant extract, causing the precipitation process. Prior to photocatalytic investigations, the physico-chemical properties of the material are analysed using TG-DTA, XRD, FE-SEM, TEM, EDAX and BET. The developed material showcase hexagonal wurtzite structure of ZnO, with face-centered-cubic phase of Ag and AgCl. All the samples exhibit aggregated, irregular rounded grains, as expected in the precipitation synthesis process. Pristine ZnO showed 15.5% degradation efficiency towards methyl orange, which was further improved by doping Ag from 0.5 to 2 mol%. The catalyst with 1 mol% Ag doping resulted in the better photocatalytic activity (26.30%), which has again improved by loading the GO (27.46%). The outcome of this study provides the new insights to GO-loaded Ag/ZnO nanocomposites by green synthesis route, in view of photocatalytic applications.